The Relationship Between Nursing Services with Inpatient Satisfaction Levels in Three Dolok Health Centers, Dolok District, Panribuan, Simalungun District, 2017 - Doortua (Science Midwifery, 2022)
Nursing service is an effort to help individuals who are healthy or sick, from birth to death in the form of increasing their knowledge, will and abilities so that these individuals can carry out spiritual activities independently and optimally. Nursing services have: an important role in health development in order to improve the degree of public health. If various public health problems are not resolved, then the goals of health development will be hampered, so there is a need for one service, namely excellent service (Zaidin, 2001 ) .The purpose of this study was to find out: The Relationship between Nursing Services and the Level of Inpatient Satisfaction at the Tiga Dolok Health Center, Dolok Panribuan District, Simalungun Regency in 2017 This type of research is an analytic survey with a cross-sequential approach. hospitalization as a target patient. The population of this study were monthly inpatients in the 2016 period in the inpatient room of the Tiga Dolok Health Center, namely 219 patients. In this study, there were 44 inpatients. The results of the clinic were based on the relationship between nursing services and the level of satisfaction of inpatients at the Tiga Dolok Health Center, Dolok Panribuan District, Simalungun Regency in 2017 with the result that the statistic p value - 0.018 Ha failed to be rejected (p value S a) , so that it can be concluded that there is a significant relationship between nursing services and the level of inpatient satisfaction at Tiga Dolok Health Center, Dolok Panribuan District, Simalungun Regency. It is hoped that this will serve as material for further study for puskesmas in improving nursing services. Improvement of nursing services is expected to be able to meet patient needs according to patient expectations.